Plasma Levels of High-Density Lipoprotein Cholesterol and Outcomes in Pulmonary Arterial Hypertension - Heresi, Gustavo A. (American Thoracic Society, 2010)
Rationale: High-density lipoprotein cholesterol (HDL-C) promotes healthy vascular function, and it is decreased in insulin resistance. Insulin resistance predisposes to pulmonary vascular disease. Objectives: We hypothesized that HDL-C is associated with clinical outcomes in pulmonary arterial hypertension (PAH). Methods: Plasma HDL-C concentrations were measured in 69 patients with PAH (age, 46.7 ± 12.9 yr; female, 90%) and 229 control subjects (age, 57 ± 13 yr; female, 48%). Clinical outcomes of interest included hospitalization for PAH, lung transplantation, and all-cause mortality. Survival and time to clinical worsening curves were derived by the Kaplan-Meier method. Cox regression modeling of outcome versus HDL-C with individual covariate adjustments was performed. Measurement and Main Results: HDL-C was low in subjects with PAH compared with control subjects (median, interquartile range: PAH: 36, 29–40 mg/dl; control subjects: 49, 40–60 mg/dl; P < 0.001). An HDL-C level of 35 mg/dl discriminated survivors from nonsurvivors, with a sensitivity of 100% and specificity of 60%. After a median follow-up of 592 days, high HDL-C was associated with decreased mortality (hazard ratio for every 5-mg/dl increase in HDL-C, 0.643; 95% confidence interval, 0.504–0.822; P = 0.001) and less clinical worsening (hazard ratio for every 5-mg/dl increase in HDL-C, 0.798; 95% confidence interval, 0.663–0.960; P = 0.02). HDL-C remained a significant predictor of survival after adjusting for cardiovascular risk factors, C-reactive protein, indices of insulin resistance, and severity of PAH (all P < 0.05). Conclusions: Low plasma HDL-C is associated with higher mortality and clinical worsening in PAH. This association does not appear to be explained by underlying cardiovascular risk factors, insulin resistance, or the severity of PAH.